Experimental research on properties and microstructures of magnesium-iron phosphate cement. (10th October 2020) - Liu, Yuantao; Chen, Bing; Qin, Zhaohui; Pen, Dong; Aminul Haque, M.
Highlights: A novel magnesium-iron phosphate cement was prepared by incorporating Fe2 O3 powder. The properties of MPC were improved with the addition of Fe2 O3 powder. Fe2 O3 enhanced the crystallization of struvite and formed some new hydrates in MPC. High curing temperature promoted the reaction between Fe2 O3 and ADP. Abstract: A novel magnesium-iron phosphate cement was prepared based on magnesium phosphate cement (MPC), by incorporating various proportions of Fe2 O3 powder as MgO powder replacement. The research mainly concentrated on the improvement of properties and optimization of microstructure, which were measured in terms of the setting time, fluidity, compressive strength and flexural strength, and analyzed by X-ray diffraction (XRD), Fourier Transform Infrared Spectrometer (FTIR), scanning electron microscopy (SEM) and thermogravimetric (TGA-DTG). Fe2 O3 powder decreased that fluidity of the fresh paste and prolonged the setting time to a value of 16 min. The mechanical property was increased with the addition of Fe2 O3 powder, and the group containing 20% Fe2 O3 powder yielded the highest 28-day compressive strength of 58.7 MPa. Fe2 O3 enhanced the crystallization of struvite, participated in the reaction and produced some new hydrates. It also had good pore-filling effect and compacted the microstructure. The analyses on the iron-phosphate system illustrated that the reaction between Fe2 O3 and ADP was promoted by high curing temperature, and confirmed that Fe2O3 could be activated in the MPC system.